Meningkatkan Kompetensi Guru dalam Menyusun Silabus dan RPP Melalui Supervisi Akademik Berkelanjutan di SMP Negeri 2 Sabang - Faridah Faridah (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2019)
The study entitled